Bone Marrow Diagnosis : an Illustrated Guide. - Gatter, Kevin (Wiley, 2014)
Bone Marrow Diagnosis is an essential resource for all those who need to report bone marrow trephine biopsies. The text will be succinct and concentrates on the core information necessary to make an accurate diagnosis. Each diagnostic entity will be accompanied by high quality images which show typical and more unusual examples of histological features. Each section will be comprehensively revised by an international team of authors. Over 900 high quality colour images will accompany each diagnostic entity. There will be coverage of cytology in sections relating to myeloid dysplasias and acute.